Der Personalverantwortliche als strategischer Partner: Persönliche Einstellung oder subjektive Norm? - Wehner, M C; Kabst, Rüdiger; Meifert, M; Cunz, L M (Zeitschrift für Betriebswirtschaft (ZfB).)

Evaluating Major Human Resource Information Systems Design Characteristics: An Empirical Analysis. - Strohmeier, S; Kabst, Rüdiger (International Journal of Business Information Systems (IJBIS).)

Evidence-based entrepreneurship (EBE): Cumulative science, action principles, and bridging the gap between science and practice. - Frese, M; Bausch, A; Schmidt, P; Rauch, A; Kabst, Rüdiger (Foundations and Trends in Entrepreneurship.)

Graduates’ Reactions to Recruitment Process Outsourcing: A Scenario-Based Study. - Wehner, M C; Giardini, A; Kabst, Rüdiger (Human Resource Management.)

Greenfield Investment versus Akquisition: Der moderierende Einfluss wahrgenommener institutioneller Unsicherheit bei der Internationalisierung von KMU. - Eiche, J; Schwens, C; Kabst, Rüdiger (Zeitschrift für Betriebswirtschaft (ZfB).)

Internationaler Joint Venture Erfolg: Eine Meta-Analyse. - Isidor, R; Schwens, C; Kabst, Rüdiger; Hornung, F (Zeitschrift für Betriebswirtschaft (ZfB).)

Testing the Circular Structure of Human Values: A Meta-Analytical Structural Equation Modelling Approach. - Steinmetz, Holger; Isidor, R; Bäuerle, N (Survey Research Methods)

A Fuzzy Decision Support Model for Natural Disaster Response under Informational Uncertainty - Wex, Felix; Schryen, Guido; Neumann, Dirk (International Journal of Information Systems for Crisis Response and Management)

Operational Emergency Response under Informational Uncertainty: A Fuzzy Optimization Model for Scheduling and Allocating Rescue Units - Wex, Felix; Schryen, Guido; Neumann, Dirk (International Conference on Information Systems for Crisis Response and Management (ISCRAM) 2012)

IS Design Thinking in Disaster Management Research - Schryen, Guido; Wex, Felix (45th Hawaii International Conference on System Sciences)

Profis im Netz: Soziale Netzwerke könnten in Unternehmen viel mehr Nutzen stiften - woran hakt es?, in: Die Zeit (12.04.2012) - Schryen, Guido (Die Zeit)

Soziale Netzwerke in Unternehmenskontexten - Potentiale und Anforderungen, in: Information Management & Consulting, to appear - Schryen, Guido (IM Information Management & Consulting)

Berufsorientierung im Übergang - Überlegungen zur curricularen Gestaltung der Bildungsarbeit im Übergangssystem - Kremer, H.-Hugo (Individuelle Förderung und berufliche Orientierung im berufsschulischen Übergangssystem - Ergebnisse aus dem Forschungs- und Entwicklungsprojekt InLab)

Funktionen und Erträge pädagogischer Diagnostik im wirtschafts- und berufspädagogischen Bereich (Editorial) - Tramm, T.; Seeber, S.; Kremer, H.-Hugo (bwp@ Berufs- und Wirtschaftspädagogik - online)

Akademisierung der Berufsbildung - Editorial - Büchter, K.; Frommberger, D.; Kremer, H.-Hugo (bwp@ Berufs- und Wirtschaftspädagogik - online)

Open Societal Innovation: The Alemannic Definition - von Lucke, Jörn; Herzberg, Johann; Kluge, Ulrike; vom Brocke, Jan; Müller, Oliver; Zimmermann, Hans-Dieter (SSRN Electronic Journal)

Business activity management for service networks in cloud environments - Janiesch, Christian; Fischer, Robin; Matzner, Martin; Müller, Oliver (Workshop on Middleware for Service Oriented Computing)

mLearning. Akzeptanz von Mobile Learning. Chancen und Probleme in der betrieblichen Bildung - Beutner, Marc; Pechuel, R. (Jahrbuch eLearning und Wissensmanagement 2013. Die Zukunft der Bildung und die Rolle der digitalen Medien)

Sympathy or strategy: social capital drivers for collaborative contributions to the IS community - Trier, Matthias; Molka-Danielsen, Judith (European Journal of Information Systems)

Blogs as Objects of Preservation: Advancing the Discussion on Significant Properties - Stepanyan, Karen; Gkotsis, George; Kalb, Hendrik; Kim, Yunhyong; Cristea, Alexandra I.; Joy, Mike; Trier, Matthias; Ross, Seamus (iPress 2012)
challenge for the digital preservation community. While the methodological frameworks for selecting these properties provide a good foundation, a continued discussion is necessary for further clarifying and improving the available methods. This paper advances earlier work by building on the existing InSPECT framework and improving its capabilities of working with complex/compound objects like blogs. The modifications enable a more thorough analysis of object structures, accentuate the differences and similarities between the framework’s two streams of analysis (i.e. Object and Stakeholder analysis) and, subsequently, improve the final reformulation of the properties. To demonstrate the applicability of the modified framework, thepaper presents a use case of a blog preservation initiative that is informed by stakeholder interviews and evaluation of structural and technological foundations of blogs. It concludes by discussing the limitations of the approach and suggesting directions for future research.
Keywords: Blogs; Weblogs; Digital Preservation; Significant Properties

Sentiment Polarization and Balance among Users in Online Social Networks - Hillmann, Robert; Trier, Matthias (AMCIS 2012 Proceedings)
Communication within online social network applications enables users to express and share sentiments electronically. Existing studies examined the existence or distribution of sentiments in online communication at a general level or in small-observed groups. Our paper extends this research by analyzing sentiment exchange within social networks from an ego-network perspective. We draw from research on social influence and social attachment to develop theories of node polarization, balance effects and sentiment mirroring within communication dyads. Our empirical analysis covers a multitude of social networks in which the sentiment valence of all messages was determined. Subsequently we studied ego-networks of focal actors (ego) and their immediate contacts. Results support our theories and indicate that actors develop polarized sentiments towards individual peers but keep sentiment in balance on the ego-network level. Further, pairs of nodes tend to establish similar attitudes towards each other leading to stable and polarized positive or negative relationships
Keywords: Social Network Analysis; Ego-Network Analysis; Node Polarization; Sentiment Dissemination

The Blogosphere as Oeuvre: Individual and Collective Influence on Bloggers - Kalb, Hendrik; Trier, Matthias (ECIS 2012 Proceedings)
Blogging has often been described as writing an online diary but, nowadays, it is more diverse and a considerable amount of blogs forms a common interconnected resource – the blogosphere – with comprehensive societal impact. While various studies have inquired social-psychological influenceson the intention to contribute to an individual blog, the perceptions related to creating such a common valuable good have not yet been focussed. Therefore, we introduce a new construct – the oeuvre of blogging – to better account for the notion of the blogosphere as a collective outcome. Furthermore, we propose a research model to inquire the influence of individual and collective beliefs on the oeuvre in comparison to short-term blogging activity. We conducted an online survey with 509 international distributed bloggers to test our model. The results of our study provide support for the importance of an oeuvre construct to explain influences on bloggers and blogging
Keywords: Blog; Blogosphere; Collective benefit; PLS; Knowledge sharing

Dissemination Patterns and Associated Network Effects of Sentiments in Social Networks - Hillmann, Robert; Trier, Matthias (Proceedings of the 2012 IEEE/ACM International Conference on Advances in Social Networks Analysis and Mining)
Communication in online social networks has been analyzed for some time regarding the expression of sentiments. So far, very little is known about the relationship between sentiments and network emergence, dissemination patternsand possible differences between positive and negative sentiments. The dissemination patterns analyzed in this study consist of network motifs based on triples of actors and the ties among them. These motifs are associated with common social network effects to derive meaningful insights about dissemination activities. The data basis includes several thousand social networks with textual messages classified according to embedded positive and negative sentiments. Based on this data, sub-networks are extracted and analyzed with a dynamic network motif analysis to determine dissemination patterns and associated network effects. Results indicate that the emergence of digital social networks exhibits a strong tendency towards reciprocity, followed by the dominance ofhierarchy as an intermediate step leading to social clustering with hubs and transitivity effects for both positive and negative sentiments to the same extend. Sentiments embedded in exchanged textual messages do only play a secondary role in network emergence and do not express differences regarding the emergence of network patterns.
Keywords: Social Network Analysis; Dynamic Network Motif Analysis; Sentiment Dissemination; Networking Effects; Triads

More health care utilization with more insurance coverage? Evidence from a latent class model with German data - Schmitz, Hendrik (Applied Economics)

Zufriedenheit der Studierenden mit den Serviceeinrichtungen einer Universität: Ergebnisse einer explorativen multivariaten Analyse - Blum, Mareike; Kraft, Manfred; Lück, Sonja (Hochschulmanagement)

Coalitional and Strategic Market Games - Brangewitz, Sonja

An Automatic Approach for Parameter Optimization of Material Flow Simulation Models based on Particle Swarm Optimization - Laroque, Christoph; Pater, Jan-Patrick
The analysis of production systems by the use of discrete, event-based simulation is widely used and accepted as decision support method. It aims either at the comparison of competitive designs or the identification of a “best possible” configuration of the simulation model. Here, combinatorial techniques of simulation and optimization methods support the user in finding optimal solutions, which typically result in long computation times and though often prohibit a practical application in today’s industry. This paper presents a fast converging procedure as a combination of a swarm heuristic, namely the particle swarm optimization, and the material flow simulation to close this gap. Faster convergence is realized by a specific extension of classic PSO implementations. First results show the applicability with a simulation reference model.

Multi-Layer Architecture for Transition of Business-Models to common Software-Tools and Optimization of the Model-Structure exemplified with Microsoft SharePoint 2010 - Lauck, Sebastian; Hartmann, Philip; Laroque, Christoph

Fast Converging, Automated Experiment Runs for Material Flow Simulations Using Distributed Computing and Combined Metaheuristics - Laroque, Christoph; Klaas, Alexander; Fischer, Jan-Hendrik; Kuntze, Mathis (Proceedings of the 2012 Winter Simulation Conference)

Application relevance of dissertations - Dangelmaier, Wilhelm

Bi-objective-optimisation of an international transportation problem for CO2-efficient schedules - Kl{\, Benjamin; Pater, Jan-Patrick; Irohara, Takashi; Xue, Yudong (International Journal of Engineering Management and Economic)
The transportation sector accounts for a considerable portion of global CO2 emissions and the demand for transport, especially for international transport, is increasing. Current approaches to reduce CO2 emission on an operational level ignore time-related objectives and focus on simultaneous optimisation of economic and ecological objectives. In general, considering the minimisation of CO2 emissions in transportation scheduling introduces a trade-off between economic and ecological concerns. The concept of eco-efficiency is important in order to evaluate the economical value and ecological quality of business decisions. Nevertheless, this concept has primarily been applied to strategic decisions. In the present paper we demonstrate the applicability of this concept to operative decisions and introduce a bi-objective evolutionary optimisation approach for the approximation of CO2-efficient schedules in an international transportation problem.

Visualization and Collaborative Editing of Simulation Models With Heterogeneous Clients - Implemented Into the Simulator d3fact - Renken, Hendrik; Eichert, Felix Alexander; Brandt, Sascha; Klaas, Alexander

Development of cost-effective spare parts logistics for a solar technology provider under monet {\ "a} rer Ber ü consideration of resulting CO2 emissions - Dangelmaier, Wilhelm; Laroque, Christoph; Delius, Robin; Streichhan, Jenny

Kontinuierliche Adaption von Lieferketten durch Leistungsbewertung und -steuerung dynamischer Geschäftsprozesse - Hartmann, Philip; Laroque, Christoph

Comparing a hybrid simulation & optimization approach with a purely stochastic optimization to increase the robustness of production plans - Fischer, Jan-Hendrik; Delius, Robin; Horstkemper, Dennis; Laroque, Christoph

Increase of robustness in production plans using a hybrid optimization and simulation approach - Laroque, Christoph; Delius, Robin; Fischer, Jan-Hendrik (International Journal on Advances in Systems and measurements)

Parallel scheduling for evolving manufacturing systems - Klöpper, Benjamin; Pater, Jan-Patrick; Dangelmaier, Wilhelm (Proceedings of the 9th IEEE International Conference on Industrial Informatics)

Building blocks of business informatics - basics and applications - Fischer, J; Dangelmaier, Wilhelm; Nastansky, Ludwig; Suhl, L

Robust solution approach to an uncertain CLSP problem - Kaganova, Ekaterina (Applied Mathematical Optimization and Modelling)

A multi-objective evolutionary approach to scheduling for evolving manufacturing systems - Kl{\, Benjamin; Pater, Jan-Patrick; Honiden, Shinichi; Dangelmaier, Wilhelm (Evolving Systems)
Persistent trends like quickly changing production programs, increasing customer individual manufacturing and Sustainable Manufacturing create complex systems of objectives in manufacturing control. Service-oriented manufacturing systems and self-optimizing manufacturing resources offer the required flexibility to consider these objectives in accordance with the current organizational and economical situation. On the downside, this increase in flexibility make the control of manufacturing systems more difficult and presents new challenges regarding the scheduling. To meet these challenges, we developed scheduling framework that supports alternative process plans and considers the internal states trajectories of resources. In order to support the user in a complex decision-making environment, evolutionary multi-objective optimization is used to generate a set of relevant schedules and an interface to select the most appropriate schedule is provided.

Cascaded Heterogeneous Simulations for Analysis of Mechatronic Systems in Large Scale Transportation Scenarios - Hassan, Bassem; Wassmann, Helene; Klaas, Alexander; Kessler, Jan Henning (Proceedings of the 2012 Emerging M&S Applications in Industry & Academia Symposium, Spring Simulation Multiconference,)

Ensuring calls to automotive suppliers with minimal costs with special consideration of liquidity {\ "a} ts-, Besch {\ "a} qualification, know-how and IT restrictions - Delius, Robin

A Cross-Level Approach To Planning Changeability in Distribution Systems - Klingebiel, Katja; Winkler, Matthes; Klaas, Alexander; Laroque, Christoph (Proceedings of the 2012 Emerging M&S Applications in Industry & Academia Symposium, Spring Simulation Multiconference)

Effektives Customer Relationship Management: Instrumente - Einführungskonzepte - Organisation - Helmke, Stefan, Stefan; Uebel, Matthias; Dangelmaier, Wilhelm

Credit risk securitization and bank soundness: Evidence from the microlevel for Europe - Michalak, Tobias C.; Uhde, André (Quarterly Review of Economics and Finance)
Using a unique sample of 749 cash and synthetic securitization transactions issued by 60 stock-listed bank holdings in the EU-13 plus Switzerland over the period from 1997 to 2007 this paper provides empirical evidence that credit risk securitization has a negative impact on the issuing banks’ financial soundness. Baseline findings hold even when controlling for likely reverse causality by employing instrumental variable techniques and substituting the accounting-based z-score ratio by market-based indicators of bank risk. Moreover, investigating the relationship between credit risk securitization and single z-score components in order to evaluate significant transmission channels proposed by relevant theoretical literature, we find a negative impact of securitization on bank profitability and capital environment as well as a positive relationship between securitization and the issuing bank's return volatility. Against the background of our empirical results we underline that the decision by the Basel Committee to enhance the new Basel III framework in the field of securitization is a step in the right direction.
Keywords: Credit risk securitization Bank soundness European banking

Cross-border bank lending - Empirical evidence on further determinants from OECD banking markets - Müller, Oliver; Uhde, André (Journal of International Financial Markets, Institutions & Money)
Employing data on foreign bank claims from 13 OECD countries on 51 emerging markets between 1993 and 2007, this study investigates specific characteristics of OECD banking markets and lending banks as new important determinants of cross-border lending. We initially provide empirical evidence that in addition to well-accepted “gravity measures”, characteristics of OECD banking markets as well as lending banks’ attributes may describe further important determinants of cross-border bank lending with regard to our sample. Building subsamples of more-developed emerging markets vs. frontier markets, addressing (non) common lender relationships and analyzing cross border lending flows during different time periods, our analysis additionally reveals that both the determinants’ explanatory power and their direction of impact notably vary with respective subsamples.
Keywords: Foreign bank claims; Gravity measures; OECD banking markets’ characteristics; Lending banks’ characteristics

Wealth effects of credit risk securitization in European Banking - Farruggio, Christian; Michalak, Tobias C.; Uhde, André (Journal of Business Finance and Accounting)
Using a unique cross‐sectional dataset of 381 cash and synthetic securitizations issued by 53 banks from the EU‐15 plus Switzerland between 1997 and 2007, this paper provides empirical evidence for time‐dependent negative wealth effects of credit risk securitization announcements in European banking. Baseline results hold when comparing estimated wealth effects with a control group of similar but non‐securitizing banks for the relevant time period. Moreover, building several sub samples we find that the nexus between credit risk securitization, the issuing banks’ overall risk exposure and wealth effects is associated with a variety of transaction‐ and bank‐specific factors.
Keywords: wealth effects; credit risk securitization; Europe; event study

Measuring the quality of banking supervision revisited - Assessments by German banks before and during the financial crisis - Paul, Stephan; Stein, Stefan; Uhde, André (Journal of Governance and Regulation)
This contribution presents and discusses main results of a new survey on the assessment of supervisory quality among German banks in 2010. In particular, it is analyzed if and how supervised banks’ perception of the quality of supervisory authorities and their instruments has changed due to the financial crisis starting in mid-2007. Subsequently, results from the recent survey are compared with findings provided by a former study carried out by the authors in 2006 (Paul, Stein and Uhde, 2008).
Keywords: banking supervision; quality; assessment; banking sector

Sovereign Risk and Bank-Specific CDS Pricing - Meine, Christian; Michalak, Tobias C.; Uhde, André
Employing time series of single-name CDS market spreads from 29 European banks located in the EU-12 plus Switzerland and the UK over the period from January 2004 through September 2010 this paper analyses the relationship between increasing sovereign risk and bank-specific CDS pricing. Results from calculating relative CDS spread deviations (model minus market spreads) initially reveal a price bubble in the European CDS market until the beginning of the financial crisis in mid-2007. From this point in time the gap narrows remarkably during the financial crisis and sovereign debt crisis period. Corresponding to these findings, the empirical analysis reveals a negative impact of sovereign risk on calculated CDS spread differentials indicating a spill-over effect between sovereign risk and bank risk and hence, a positive effect on bank-specific CDS pricing. Further analyses reveal that the perception of sovereign risk is not crisis- but country-dependent suggesting that bank-specific CDS market spreads may already include a premium to cover sovereign risk from PIIGS countries during the pre-crisis period in Europe.
Keywords: Sovereign risk; Structural credit risk models; bank-specific CDS pricing

Wertorientierte Vergütung des Aufsichtsrats - Auswirkungen auf den Unternehmenswert - Ebert, Michael; Zein, Nicole (Betriebswirtschaftliche Forschung und Praxis)

Der Einfluss der Zinsschranke auf unternehmerische Kapitalstrukturentscheidungen - Maßbaum, Alexandra; Klotzkowski, Tasja; Sureth-Sloane, Caren (Zeitschrift für Betriebswirtschaft)

Does insider shareholding matter to corporate payout reactions to tax reforms? - Sureth-Sloane, Caren (Zeitschrift für Betriebswirtschaft)

Editorial: What Is and What Is Not a Substantial Contribution? - Albers, Sönke; Sureth, Caren (Business Research)

I thought it was all over and now it is back again – Customer reactions to time extensions of sales promotions - Garnefeld, I.; Münkhoff, Eva; Bruns, A. (2012 AMA Summer Academic Conference, Chicago, IL)

Growing with industrial services – A configurational approach (ausgezeichnet mit Best Paper Award) - Eggert, A.; Münkhoff, Eva; Thiesbrummel, C. (2012 AMA Winter Academic Conference, St. Petersburg, FL)

Die Messung von Joint-Venture-Erfolg - Isidor, Rodrigo; Schwens, Christian; Kabst, Rüdiger (Markteintrittsstrategien)

Die Messung von Joint-Venture-Erfolg - Isidor, Rodrigo; Schwens, Christian; Kabst, Rüdiger (Markteintrittsstrategien)

Die Messung von Joint-Venture-Erfolg - Isidor, Rodrigo; Schwens, Christian; Kabst, Rüdiger (Markteintrittsstrategien)

Determinants of different types of born globals - Baum, Matthias; Schwens, C.; Kabst, Rüdiger (Handbook of Research on Born Globals)

Determinants of different types of born globals - Baum, Matthias; Schwens, C.; Kabst, Rüdiger (Handbook of Research on Born Globals)

Transport- und Bestellmengenplanung in Supply Chains - Harborth, Oliver (Entscheidungsprobleme im Supply Chain Management - Quantitative Lösungsansätze für den Mittelstand -)

Financial Chain Management als Koordinationsinstrument für Investitionsprojekte in Supply Chains - Heitmann, Ingmar (Entscheidungsprobleme im Supply Chain Management - Quantitative Lösungsansätze für den Mittelstand -)

Segmentspezifische und multikriterielle Bewertung von Standorten international agierender Unternehmen - Koch, Christian

Value Based Supply Chain Management (VBSCM) - Opitz, Oliver (Entscheidungsprobleme im Supply Chain Management - Quantitative Lösungsansätze für den Mittelstand)

Value Based Supply Chain Management (VBSCM) - Faupel, Christian (Entscheidungsprobleme im Supply Chain Management - Quantitative Lösungsansätze für den Mittelstand)

The Bright and Dark Side of Endowed Status in Hierarchical Loyalty Programs - Eggert, A.; Garnefeld, I.; Steinhoff, Lena (2012 AMA Summer Marketing Educators’ Conference Proceedings, Chicago)

Endowed Status in Hierarchical Loyalty Programs - Eggert, A.; Garnefeld, I.; Steinhoff, Lena (2012 AMA Winter Marketing Educators’ Conference Proceedings, St. Petersburg)

Sovereign risk and bank-specific CDS pricing - Uhde, André; Michalak, Tobias; Meine, Christian
Employing time series of single-name CDS market spreads from 29 European banks located in the EU-12 plus Switzerland and the UK over the period from January 2004 through September 2010 this paper analyses the relationship between increasing sovereign risk and bank-specific CDS pricing. Results from calculating relative CDS spread deviations (model minus market spreads) initially reveal a price bubble in the European CDS market until the beginning of the financial crisis in mid-2007. From this point in time the gap narrows remarkably during the financial crisis and sovereign debt crisis period. Corresponding to these findings, the empirical analysis reveals a negative impact of sovereign risk on calculated CDS spread differentials indicating a spill-over effect between sovereign risk and bank risk and hence, a positive effect on bank-specific CDS pricing. Further analyses reveal that the perception of sovereign risk is not crisis- but country-dependent suggesting that bank-specific CDS market spreads may already include a premium to cover sovereign risk from PIIGS countries during the pre-crisis period in Europe.

Proportionality and the power of unequal parties - Dimitrov, Dinko; Haake, Claus-Jochen (International Journal of Economic Theory)
In this paper we introduce the concept of an overall power function that is meant to combine two sources of a party’s power in a parliament. The first source is based on the possibilities for the party to be part of a majority coalition and it is typically modeled using a cooperative simple game. The second source takes into account parties’ asymmetries outside the cooperative game and it is displayed by a vector of exogenously given weights. We adopt a normative point of view and provide an axiomatic characterization of a specific overall power function, in which the weights enter in a proportional fashion.

Internationale Standortwahl als strategisches Logistikproblem - Betz, Stefan (Ausgewählte Probleme des Logistikmanagements)

Bedarfsorientiertes Kapazitätsmanagement in Supply Chains - Betz, Stefan (Ausgewählte Probleme des Logistikmanagements)

Zur Bewertung von Verlustgesellschaften nach den Änderungen des §8c KStG durch das Wachstumsbeschleunigungsgesetz - Diller, M.; Kundisch, Dennis; Späth, T. (CORPORATE FINANCE biz)

Ausgewählte Probleme des Logistikmanagements

Internationale Umweltpolitik bei akkumulierender und asymmetrischer Verschmutzungsdynamik - Gries, Thomas (Zukunftsfähige Wirtschaftspolitik für Deutschland und Europa)

Conceptualizing Service Network Productivity --- A Looped DEA Approach - Becker, Jörg; Beverungen, Daniel; Breuker, Dominic (XII European Workshop on Efficiency and Productivity Analysis (Abstract))

How to Model Service Productivity for Data Envelopment Analysis? A Meta-Design Approach - Becker, Jörg; Beverungen, Daniel; Breuker, Dominic; Dietrich, Hanns-Alexander; Knackstedt, Ralf; Peter Rauer, Hans (ECIS 2011 Proceedings)

Do we need new theories on service productivity? --- Status Quo and implications from contemporary research - Becker, Jörg; Beverungen, Daniel; Knackstedt, Ralf; Dietrich, Hanns-Alexander; Breuker, Dominic; Peter Rauer, Hans; Sigge, Daniel (XXI. International RESER Conference)

Information Needs in Service Systems --- A Framework for Integrating Service and Manufacturing Business Processes - Becker, Jörg; Beverungen, Daniel; Knackstedt, Ralf; Matzner, Martin; Müller, Oliver (Proceedings of the 44th Annual Hawaii International Conference on System Sciences)

Design Science in Service Research: A Framework-Based Review of IT Artifacts in Germany - Becker, Jörg; Beverungen, Daniel; Matzner, Martin; Müller, Oliver; Pöppelbuß, Jens (International Conference on Design Science Research in Information Systems and Technology)

Mapping the Emerging Field of Service Science: Insights from a Citation Network and Cocitation Network Analysis - Beverungen, Daniel (32th International Conference on Information Systems (ICIS))

The Morphology of Service Bundling Settings - Beverungen, Daniel; Kohlborn, Thomas; Fielt, Erwin (22nd Australasian Conference on Information Systems (ACIS))

Where are the participants? Including motivational aspects into theorizing and design in IS Research - Beverungen, Daniel; Wittchen, Marion; Becker, Jörg (Proceedings of the 19th European Conference on Information Systems)

On the Coalescence of Supply Networks and Information Systems - Hellingrath, Bernd; Becker, Jörg; Beverungen, Daniel; Böhle, Carsten; Räckers, Michael (EMNet)

Pricing of Value Bundles: A Multi-Perspective Decision Support Approach - Becker, Jörg; Beverungen, Daniel; Knackstedt, Ralf; Müller, Oliver (Enterprise Modelling and Information Systems Architectures)

Entrepreneurship and human development - A capability approach - Gries, Thomas; Naudé, Wim (Journal of Public Economics)

Entrepreneurship, Structural Change and a Global Economic Crisis - Gries, Thomas; Naudé, Wim (Entrepreneurship Research Journal)

SME performance in transition economies: The financial regulation and firm level corruption nexus - Gries, Thomas; Wieneke, Axel (Journal of Comparative Economics)

Income Determination and Income Discrimination in Shenzhen - Gries, Thomas; Gravemeyer, Stefan; Xue, Jinjun (Urban Studies)

Financial Deepening, Trade Openness and Economic Growth in Latin America and the Caribbean - Gries, Thomas; Kraft, Manfred; Meierrieks, Daniel (Applied Economics)

Causal Linkages Between Domestic Terrorism and Economic Growth - Gries, Thomas; Krieger, Tim; Meierrieks, Daniel (Defence and Peace Economics)

Interregional Migration, Self-selection and the Returns to Education in Brazil - Gries, Thomas; Kraft, Manfred; Piek, Christina (The Annals of Regional Science)

Trade Openness and Economic Growth: A Panel Causality Analysis - Gries, Thomas; Redlin, Margarete

The Impact of Delegating Decision Making to IT on the Sunk Cost Effect - Herrmann, Philipp; Kundisch, Dennis; Rahman, Mohammad (12th Workshop on Information Systems and Economics (WISE))

Sunk Cost Effect: The Impact of Delegating Decision Making to IT - Herrmann, Philipp; Kundisch, Dennis; Rahman, Mohammad (INFORMS 2011 Annual Meeting, Track Digital Channel and It Usage)

Sunk Cost Effect: The Impact of Delegating Decision Making to IT - Herrmann, Philipp; Kundisch, Dennis; Rahman, Mohammad (7th Symposium on Statistical Challenges in Electronic Commerce Research)

A new Perspective on Resource Interactions in IT/IS Project Portfolio Selection - Kundisch, Dennis; Meier, Christian (Proceedings of the European Conference on Information Systems (ECIS))

The Impact of Interaction Effects Among Software Development Projects on Global Sourcing Decisions - Heinrich, B.; Kundisch, Dennis; Zimmermann, Steffen (5th Global Sourcing Workshop)

IT/IS Project Portfolio Selection in the Presence of Project Interactions - Review and Synthesis of the Literature - Kundisch, Dennis; Meier, Christian (Wirtschaftsinformatik Proceedings)

Partizipieren statt konsumieren, oder: Lohnt sich Engagement in Q&A-Communities? - Herrmann, Philipp; Kundisch, Dennis (Wirtschaftsinformatik Proceedings)

Unternehmensbewertung in Deutschland: Verfahren, Finanzplanung und Kapitalkostenermittlung - Sievers, Sönke; Homburg, Carsten; Lorenz, Michael (Controlling & Management Review (VHB-JOURQUAL 3 Ranking D))